Feelings of nurses faced with death: pleasure and suffering from the perspective of psychodynamics of Dejours - Janaína Luiza dos Santos; Sabrina Corral Mulato; Sonia Maria Villela Bueno; Maria Lucia do Carmo Cruz Robazzi (Universidad de Antioquia, 2016)
Objective. To analyze the feelings of nurses confronting death, according to the Dejourian psychodynamic. Methods. This is a qualitative, exploratory study, analyzed, interpreted and discussed emphasizing the suffering and pleasure, proposed by Dejours. Results. Participants were 11 nurses, mostly woman, single, white, Catholic, between two sixteen years of profession. The analysis of responses allowed finding some driving and potentiating factors of feelings of pleasure and suffering. It was identified as pleasure: feeling of accomplishment, comfort and relief; as suffering, sadness, frustration, difficulty with grief, impotence and incapacity. They also have defense mechanisms to prevent suffering, as not to think about suffering and death, taking refuge in work. Conclusion. The factors related to the pleasure and the pain of Nurses when facing death were identified. Therefore, education is necessary regarding the process of death in academic training and studies that approach the nurse to this natural process.   How to cite this article:  Dos Santos JL, Corral-Mulato S, Bueno SMV, Robazzi MLCC. Feelings of nurses faced with death: pleasure and suffering from the perspective of psychodynamics of Dejours. Invest. Educ. Enferm. 2016; 34(3): 511-517.